Art Education Phenomena in the School Environment (a Case Study of the Application of Art Education in a School Environment) - Arsan Shanie (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2020)
Art education exists to help transfer knowledge and attitudes to students and is not to be seen as mere leisure time. Writing this article aims to restore the function of art education to its original function. The method in this study using the Literature method. The results of the research are, first, art is the result of imitation of nature in the form of creativity, feeling and human intention or human ability to do something, in the form of an expression of the artist's activity process starting from physical activity that comes from human feelings and is beautiful so that it can move the human soul and feelings. Second, art education is not present to create students who are experts in the field of art but to foster aesthetic and artistic sensitivity to form critical, appreciative, and creative attitudes in students as a whole. Third, the right approach or method to find out that children have aesthetic experiences using an action-based approach. Fourth, the benefits of art education are as a means to instill aesthetic values, by means of art education students have aesthetic sensitivity. Fifth, the aim of Art Education is not to educate students to become artists.